80.4k views
3 votes
2x - 3y = 12
x = 4y + 1

User Curline
by
6.2k points

1 Answer

4 votes

Answer:

x = 9, y = 2 is the solution of the given system.

Explanation:

Here, the given set of equation is :

2 x - 3 y = 12

x = 4 y + 1

Now, from equation (2) we see that x = 4 y + 1.

Substitute the value of y from (2) in the first equation. we get:

2 x - 3 y = 12 ⇒ 2 (4 y + 1) - 3 y = 12

or, 8 y + 2 - 3 y = 12

or, 5 y = 12- 2 = 10

or, y = 10/ 5 = 2

or, y = 2

Now, x = 4 y + 1 ⇒ x = 4(2) + 1 = 8 + 1 = 9, or x = 9

Hence, x = 9, y = 2 is the solution of the given system.

User Lars Grammel
by
5.7k points